Analisis Pengaruh Hafalan Al-Qur'an Terhadap Prestasi Belajar Siswa Di Ma Al-Amiriyyah Blokagung Banyuwangi - Mahmudah Mahmudah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
The purpose of this study is to analyze the effect of memorization of al-Qur'an on mathematics learning achievement of students of class XI Agama semester odd academic year 2015-2016 at MA Al-Amiriyyah Blokagung Banyuwangi. With the number of respondents for Religion class 1 27 students and 2 Religion students 31 students. The method used is a quantitative method. In the data collection using the method of observation, questionnaires/questionnaires, and documentation. The data analysis used is a simple linear regression with the help of Statistical Product and Service Solution (SPSS) Software. The results of the analysis of data obtained, in class XI Religion memorization al-Qur'an gives the effect of 0.756 or 24.4% of mathematics learning achievement, the remaining 24.4% caused by other factors. Therefore there is an influence between the recitation of al-Qur'an on mathematics learning achievement of students of class XI The odd semester of the academic year 2015-2016 at MA Al-Amiriyyah Blokagung Banyuwangi